Evaluation of the Antioxidant Effectiveness in Reduction of the Dry Eye Syndrome among Patients with Relevant Toxicoallergic Component and a Severe Case of Corneal-Conjunctival Xerosis - D. Yu. Maychuk; A. O. Loshkareva; A. A. Tarkhanova (Oftalʹmologiâ)
Currently the ophthalmologists meet with corneal-conjunctival xerosis more often in their daily practice. The objective of this research is identifying a new alternative method of treatment of the dry eye syndrome of different severity. In this work there will be a demonstration and the results of usage of BAA Delphanto® in treatment of different cases of the dry eye syndrome. The data collected from a dynamic research of groups of patients reveals the effectiveness of the comprehensive therapy with the use of BAA Delphanto®. Consequently, the research results demonstrate an improvement of the initial data from the biomicroscopy, OSDI index, Schirmer-1 test and the tear break up time. The statistically significant results were received reveal the effectiveness of the use of BAA Delphanto® with a significant improvement of the quality of life. It can be used widely by ophthalmologists for the treatment of corneal-conjunctival xerosis of different severity.